The Right of The Individual to The Safety of His physical and Psychological Being During the Investigation in Accordance with International Conventions and Islamic Law (Comparative Study) - Abdelgadir, Abdelgadir Abdelrhman (Journal of Economic, Administrative and Legal Sciences, 2023)
In this study, the researcher dealt with the issue of psychological and physical harm to some people while they are under criminal investigation in cases where law enforcement agencies seek to obtain certain information or confessions, as when circumstances require obtaining criminal evidence, such as obligatory blood sampling, to detect alcohol or narcotic abuse. The study exposes the abuses that occur by the law enforcement officials in violation of the provisions of constitutional systems, and general principles of human rights stipulated in international conventions and treaties. The use of illegal force against arrested persons, prisoners and prisoners of war is a flagrant violation and waste of human dignity, and at the same time it constitutes an abuse of power and influence. Torture is one of the legacies of the old previous eras, and a manifestation of their power, because the investigative agencies in those eras are often loyal to the governing authority, and not to the legal system based on the constitution or lofty human values. However, with the development of human relations, and the knowledge’s exchange between nations and peoples, humanity has created systems and rules through which the principles of justice and respect for individual rights prevail, and that every person has the right to enjoy his rights and share of dignity as authentically rights. The last decades of the last century witnessed a boom in human rights legislation that led to the obligation of states and governments to the principles of legality and respect for the principle of the rule of law. This principle is evident in the regulatory guarantees that limit the authorities’ excessiveness in interfering with the freedoms of individuals or harming their dignity if they are subject to police control procedures, which were common practices in eras when the legislation regulating human rights was not mature enough.